PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T. (The Accounting Review, 1940)
The problems mentioned in the paper were presented as the second half of the November 1939 C.P.A. examination prepared by the Board of Examiners of the American Institute of Accountants. The candidates were required to solve all problems in six hours. The weights were as follows: problem 1, 10 points; problem 2, 25 points; problem 3, 30 points, and problem 4, 33 points. The set of problems which, while far from an ideal C.P.A. examination, is superior to Part I of the same examination, which appeared in the December issue of the journal The Accounting Review. Unlike problem 3 of part 1, the problems of this set are clearly stated and lead to a solution without imposing on the candidate the added burden of reading the mind of the examiner.